Peran Fatwa dalam Menyusun Qanun: Tinjauan Fiqh dan Implikasinya dalam Praktik Hukum - Ai Reni Ratnasari; Fakhry Fadhil (STAI Al-Mas'udiyah, 2025)
The main issue in this study is how the role of fatwa in the process of drafting qanun, as well as its implications in legal practice, especially in the context of the relationship between fiqh, fatwa, and qanun. The purpose of this study is to analyze the interaction between fiqh, fatwa, and qanun in the Islamic legal system, as well as to explore how fatwa can influence legal policies in line with Islamic principles. The research method used is a qualitative approach through literature study analysis and case studies, focusing on the application of fatwa in qanun, particularly in Indonesia. The main results achieved show that fiqh provides the basis for issuing practical fatwas, which then become the basis for drafting qanuns. Although fatwas are not legally binding, they have an important role in shaping public policy, influencing social norms, and providing legitimacy to legislation based on Islamic principles, as seen in MUI fatwas related to zakat and halal products. However, the implementation of fatwa in qanun faces major challenges, such as constitutionality, public acceptance, and the low level of fatwa socialization.